Perovskite solar cell-thermoelectric tandem system with a high efficiency of over 23%. (June 2019) - Zhou, Yangying; Yin, Xuewen; Zhang, Qi; Wang, Ning; Yamamoto, Atsushi; Koumoto, Kunihito; Shen, Heping; Lin, Hong
Abstract: Photovoltaic-thermoelectric (PV-TE) tandem system has been considered as a viable approach to fully exploit solar energy by making full use of both solar light and solar heat generation. Herein, we demonstrate an efficient perovskite solar cell (PSC)-thermoelectric (TE) hybrid system with four-terminal configuration. To balance the light-to-electricity and heat-to-electricity efficiency and ultimately realize high solar energy conversion efficiency, we performed both simulation and experiment by tuning the bandgap of top PSC. Using perovskite with a composition of CH3 NH3 Pb(I0.95 Br0.05 )3 (band gap: 1.61 eV), we achieved a state-of-the-art efficiency of over 23%, with 18.3% from the PSC and the rest contributed by heat conversion using TE module. Our work proves that the low-grade heat produced by PSCs can be recovered and utilized by thermoelectric modules, and provides a promising route to improve the utilization rate of solar radiation based on PSCs. Highlights: The low-grade heat produced by PSCs is utilized by thermoelectric modules. A high efficiency of over 23% in PSC-TE tandem system is achieved. Both simulation and experiments of PSC-TE tandem system are performed.